2016
DOI: 10.5001/omj.2016.66
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Substance Use: Study in a De-addiction Clinic

Abstract: A high proportion of poly-substance use was found in the study population. Our findings could help in the management and development of prevention strategies for substance use in Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 4 publications
5
13
0
Order By: Relevance
“…The findings are comparable to findings of other studies. [9][10][11][12][13][14][15][16][17][18] In the present study, majority (62.40%) of the participants were single (unmarried/separated/divorced). This finding was similar with other studies conducted around the different part of the country.…”
Section: Discussionmentioning
confidence: 99%
“…The findings are comparable to findings of other studies. [9][10][11][12][13][14][15][16][17][18] In the present study, majority (62.40%) of the participants were single (unmarried/separated/divorced). This finding was similar with other studies conducted around the different part of the country.…”
Section: Discussionmentioning
confidence: 99%
“…The Bangladesh Bureau of Statistics, 2013 found that 20-34 years was the age of initiation for most (47.3%) intoxicating substance abusers and 33% of abusers started between 15-19 years old [17]. A study conducted in the outpatient department of National Institute of Mental Health in Dhaka, revealed that 7.66% of respondents suffered from a substance-related disorder [18].…”
Section: Prevalence Of Addiction In Bangladeshmentioning
confidence: 99%
“…Similar to earlier study Kumar et al conducted in Indian settings we can infer that alcohol is the commonest drug of abuse followed by tobacco. 10 Consumption of the traditional drugs like opium and cannabis were remarkably low as compared to alcohol and tobacco, which is near about in range of their use reported from other study Dadwani et al, Maruf et al 18,20 It showed effects of urbanization and shifting from traditional way of life to modern life.…”
Section: Discussionmentioning
confidence: 91%